Efetividade do exercício resistido no índice de atividade motora diária e na capacidade funcional em mulheres com síndrome de Sjögren primária: ensaio clínico randomizado - Minali, Paulo Alexandre [UNIFESP] (2018)
Introduction: Primary Sjögren syndrome (pSS) is an autoimmune inflammatory systemic disease that affects exocrine glands and less frequently internal organs. Inflammation can affect any system, including the musculoskeletal system, resulting in reduction in physical functions with consequent decrease in muscle strength, aerobic capacity, joint mobility, and static balance. In addition, psychosocial impairment with potential worsening of quality of life and functional capacity (FC) is described. Finally, patients with pSS also present a high level of fatigue, which is a distinct physiological characteristic of this disease. Objective: Analyze the effectiveness of resistance exercise on daily motor behavior and functional capacity in women with pSS. Methods: Fifty nine patients were randomized; of which 51 completed the study (26 assigned to the exercise group - EXG and 25 to the control group - CG). The EXG participated in a 16 week supervised exercise program, including 2 sessions per week and 3 sets of 10 maximal repetitions per exercise. Both before and at the end of the intervention protocol four variables were evaluated: the daily motor activity index (DMAI) was analyzed by an actigraphy, which records body movements; the FC (Fullerton Functional Fitness Test - consists of a sequence of 6 tests that mimic the neuromotor and cardiorespiratory needs involved in the activities of daily life: upper limb (MMSS) and lower limb strength (MMII), flexibility of MMSS and MMII, aerobic capacity and motor agility, and the DASH questionnaire - estimated FC from MMSS); the disease activity (ESSDAI questionnaire); and quality of life (SF-36 questionnaire). Results: After the intervention period in the GEX group, all FC parameters showed improvement over basal and final times, except the MMSS flexibility test (p=0.896): MMSS strength (p<0.001), MMII strength (p<0.001), MMII flexibility (p=0.001), aerobic capacity (p<0.001), agility (p=0.002), and the DASH (p<0.001). A similar situation occurred with the SF-36 where all domains improved, except for the emotional aspect (p=0.710): functional capacity (p<0.001), limitation by physical aspects (p=0.005), pain (p<0.001), general condition (p=0.006), vitality (p<0.001), social aspects (p=0.001), and mental health (p<0.001). There was no change in the DMAI (p=0.2) or ESSDAI (p=0.284). However, from the perspective of the movement of patients among the categories or classification levels of the ESSDAI, the GEX showed improvement while the CTRL worsened. Conclusion: Fourteen (82,3%) of the 17 variables evaluated showed improvement after the intervention. The four-month supervised resistance exercise program with two weekly sessions did not worsen the DMAI or disease activity, suggesting a protective effect of the intervention, and was effective in improving functional capacity and quality of life in women with pSS.